2018
DOI: 10.1097/jcp.0000000000000941
|View full text |Cite
|
Sign up to set email alerts
|

Digit Symbol Substitution Test

Abstract: The DSST is sensitive to the presence of cognitive dysfunction as well as to change in cognitive function across a wide range of clinical populations but has low specificity to determine exactly which cognitive domain has been affected. However, the DSST offers a practical and effective method to monitor cognitive functions over time in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
284
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 563 publications
(290 citation statements)
references
References 50 publications
2
284
1
3
Order By: Relevance
“…A significant improvement was noted in both of the visual processing speed tests (TMT A and DSST). Performance on the DSST could be influenced by associative learning, potentially explaining the observed similarities in the pattern of cognitive improvement [22]. In contrast, no significant changes in Digit Span test were noted.…”
Section: Discussionmentioning
confidence: 91%
“…A significant improvement was noted in both of the visual processing speed tests (TMT A and DSST). Performance on the DSST could be influenced by associative learning, potentially explaining the observed similarities in the pattern of cognitive improvement [22]. In contrast, no significant changes in Digit Span test were noted.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, recent study findings showed that a one-unit decrease in the information processing speed test, as assessed using a digit symbol score, increased the incidence of CF by 33.2%. The digit symbol task has been shown to be a sensitive method for detecting the decrements in cognitive function, specifically in the processing speed among older people with DM and depression [60,61]. Moreover, the association of a smaller volume of the pre-frontal area with a slow gait speed was explained by the lower performance in the digit symbol test [9].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to VF, the DSST measures speed of information processing and attention, but the contribution of working memory and executive functions is not negligible. The DSST is very sensitive but less specific to a wide range of impairments and is especially suitable for the detection of longitudinal cognitive changes in psychiatric disorders [43]. The dissociation among RMET (improved), VF (stable), and DSST (worsened) is surprising, suggesting that distinct cognitive domains display an altered pattern of changes during the course schizophrenia.…”
Section: Discussionmentioning
confidence: 99%